(untitled) (Revista Contexto & Saúde, 2023)
OBJECTIVE: To analyze the potential clinical impact of unintended medication discrepancies to which pediatric patients are exposed on hospital admission. METHODS: Descriptive observational study, conducted at the pediatric emergency unit of a university hospital, from April to August 2019. The included patients werw aged 28 days to 12 years and werw approached within 48 hours of admission. An interview was carried out with the children and their companions and their prescriptions (home and hospital) were reconciled. The discrepancies found were classified as intentional, intentional undocumented and unintentional. Descriptive analysis was performed to characterize the profile of the sample, unintentional discrepancies and the potential to harm the errors involved. The harmful potential of medication errors was assessed by a panel of eleven specialist pharmacists. RESULTS: 69 patients were included, with a median age of 3 years, 55% male. A total of 252 medications were reconciled, with 53 (21%) involved in medication error. Almost half of the patients (41%; N=28) had at least one medication error on hospital admission, with omission being the most prevalent (45%; N=24). If these errors had not been detected, 58% (N=31) of them could have caused harmful harm to patients (Level 3) and 34% (N=18) required further monitoring or intervention to prevent harm (Level 2).CONCLUSION: The study demonstrates a high frequency of unintended discrepancies that were classified as potential damage in pediatric patients.